Exploring English Language Teaching Method of the Second Grade Students at SMA MBS Yogyakarta - Dina Ayu Puspitasari (Metathesis: Journal of English Language, Literature, and Teaching, 2019)
The purposes of this study are: 1) to find out the method to teach English subject at SMA MBS Yogyakarta. 2) to find out the different method employed by English teachers in teaching English subject. 3) to find out the difficulties faced by the English teachers in teaching English subject. The design of this study is descriptive qualitative research. The object of this study is all of English teachers of the second grade students. The data was taken from interviews and classroom observations. In the data analysis techniques, the results of interviews with all of English teachers are grouped into the observed topic. The result of this study shows that the method used by English teachers in teaching English subject is the eclectic method. There are no different methods in teaching English subject. The difficulties encountered by the English teachers in teaching English subject include classroom management, and limited learning sources.